The Influence of Students' Activeness in Youth Red Cross Extracurriculars on Landslide Disaster Preparedness at Senior High School 1 Plaosan, Magetan Regency - Halimah, Siti Nur; Susilawati, Siti Azizah (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: this research aims to analyze the influence of students' activeness in the Youth Red Cross extracurricular on landslide disaster preparedness at Senior High School1 Plaosan, Magetan Regency. Methodology: The research employed a quantitative approach with a correlation regression design. The population in this study was all Youth Red Cross members, totaling 50 students. The sample comprised all Youth Red Cross members, constituting the research sample. Data collection in this study used questionnaires which had to be filled in by all respondents. Results: The results of this research are the first results of calculating the highest student activity, namely the active criteria with a percentage value of 32%. Out of the total sample, there were 16 active students. The analysis categorized the landslide disaster preparedness at Senior High School Negeri 1 Plaosan into the 'ready' category, with an overall percentage of 79%. The third result indicates a linear relationship between students' activity in the Youth Red Cross extracurricular and landslide disaster preparedness at Senior High School 1 Plaosan, Magetan Regency. The results of data analysis show a correlation value of 0.919, it can be said that there is a perfect and positive correlation between the two variables of student activity in the Youth Red Cross extracurricular towards landslide disaster preparedness. Applications/Originality/Value: This research demonstrates the influence of student activity in extracurriculars on landslide disaster preparedness at Senior High School 1 Plaosan.